Method for determining of the distance to the object in the hyperbolic navigation system via doppler frequency offsets - V. V. Legkostup; V. E. Markevich (Системный анализ и прикладная информатика)
In this paper, a method for estimating the distance to the object guided along a hyperbola to a target using a bistatic hyperbolic navigation system on a plane is given. At the same time, to solve the guidance problem, the number of required navigation positions is reduced by one in comparison with the classical method of hyperbolic navigation. However, in the guidance algorithms, it is still required to estimate the distance of the targeted object from the center of the base, the methods of obtaining which are considered in the work.